Experimental particle physics : understanding the measurements and searches at the Large Hadron Collider - Kar, Deepak; Suri, Jasjit S. (IOP (Series). Release 6., 2019)
This book is written for advanced undergraduate or beginning postgraduate student starting data analysis in experimental particle physics, more specifically at the Large Hadron Collider (LHC) at CERN. Only assuming basic knowledge of quantum mechanics and special relativity, it recaps the current state of affairs in particle physics, before comprehensively introducing all the ingredients that go into an analysis. Including how each we go from electronic signals in the detectors to visualising what particles were produced in a collision, and how we determine if that is consistent with Standard Model predictions or indicate the presence of yet unseen particles. The results are usually represented in what we call plots, and the book ensures students can understand what goes into the making of the plots, and how to interpret them.